Psychiatric injury in the workplace: an analysis under the Islamic principles and the law of torts - Ambaras Khan, Mushera Bibi; Sardar Baig, Farheen Baig (2019)
In recent years, claims for damages for deliberately or negligently inflicted psychiatric illness have succeeded against employers. In the case of Mount Isa Mines v Pusey, the court decided that an employer’s duty of care towards the employees is not limited to cases of physical injury but also extended to cases of psychiatric injury. In order to claim damages for psychiatric injury, the law of torts requires the plaintiff to prove two elements: namely, reasonable forseeability and proximity. This paper examines on the two elements as required under the law in the context of psychiatric illness in the workplace. The paper analyses cases from UK, Malaysia and Australia, elaborating on how an employee can successfully bring an action against his/her employer for his/her psychiatric illness suffered at the workplace.The author employs doctrinal analysis from primary and secondary legal sources in arriving at the solutions to the above problem. This paper will significantly contribute to the existing literature by discussing the challenges faced by an employee in proving the conditions required by the law and its solutions to ensure that employee who suffered psychiatric illness in the workplace has a redress under the law of torts. This paper also considers the scenario from an Islamic perspective in order to shed light on the seriousness of the welfare of employee guaranteed by the religion.